In vitro import of cytochrome c peroxidase into the intermembrane space: release of the processed form by intact mitochondria (The Rockefeller University Press, 1989)
Cytochrome c peroxidase (CCP) is a nuclearly encoded hemoprotein located in the intermembrane space (IMS) of Saccharomyces cerevisiae mitochondria. Wild-type preCCP synthesized in rabbit reticulocyte lysates, however, was inefficiently translocated into isolated mitochondria and was inherently resistant to externally added proteases. To test whether premature heme addition to the apoprecursor was responsible for the protease resistance and the inability to import preCCP, site-directed mutagenesis was used to replace the axial heme ligand (His175) involved in forming a pseudo-covalent link between the heme iron and CCP. Mutant proteins containing Leu, Arg, Met, or Pro at residue 175 of mature CCP were sensitive to proteolysis and were imported into isolated mitochondria as judged by proteolytic processing of the precursor. The inhibition of wild-type CCP translocation across the outer membrane may result from the inability of the heme-containing protein to unfold during the translocation process. Although the protease responsible for cleaving preCCP to its mature form is believed to be located in the IMS, most of the processed CCP was located in the supernatant rather than the mitochondrial pellet. Since the outer membranes were shown to be intact, the anomalous localization indicated that preCCP may not have been completely translocated into the IMS before proteolytic processing or that conformationally labile proteins may not be retained by the outer membrane. Proteolytic maturation of preCCP also occurred in the presence of valinomycin, suggesting that the precursor may be completely or partially translocated across the outer mitochondrial membrane independent of a potential across the inner mitochondrial membrane.